2017
DOI: 10.1021/acsnano.7b06242
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Photoexcited Carriers in Hybrid Perovskite Semiconductors: Trap-Dominated Spatial Heterogeneity and Diffusion

Abstract: We use correlated confocal and wide-field fluorescence microscopy to probe the interplay between local variations in charge carrier recombination and charge carrier transport in methylammonium lead triiodide perovskite thin films. We find that local photoluminescence variations present in confocal imaging are also observed in wide-field imaging, while intensity-dependent confocal measurements show that the heterogeneity in nonradiative losses observed at low excitation powers becomes less pronounced at higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
164
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(178 citation statements)
references
References 57 publications
14
164
0
Order By: Relevance
“…As stated earlier, understanding grain boundary properties has been critical to the development of many other photovoltaic semiconductor technologies such as CdTe, GaAs, InP, and Cu(In1-xGax)Se2, [22][23][24][25][26][27][28][29] and indeed other materials, such as high temperature polycrystalline superconductors. 45,46 We anticipate that understanding the nature of the different grain boundaries identified by EBSD will be critical to understanding the properties of halide perovskite photovoltaics, 21 and we speculate that properties such as anisotropic charge carrier transport across grain boundaries observed in halide perovskites 13,[47][48][49] could depend on grain boundary properties such as misorientation angle, type of boundary, and the boundary interface energy.…”
Section: Figure 2 Imaging the Local Orientation Heterogeneity Grainmentioning
confidence: 99%
See 1 more Smart Citation
“…As stated earlier, understanding grain boundary properties has been critical to the development of many other photovoltaic semiconductor technologies such as CdTe, GaAs, InP, and Cu(In1-xGax)Se2, [22][23][24][25][26][27][28][29] and indeed other materials, such as high temperature polycrystalline superconductors. 45,46 We anticipate that understanding the nature of the different grain boundaries identified by EBSD will be critical to understanding the properties of halide perovskite photovoltaics, 21 and we speculate that properties such as anisotropic charge carrier transport across grain boundaries observed in halide perovskites 13,[47][48][49] could depend on grain boundary properties such as misorientation angle, type of boundary, and the boundary interface energy.…”
Section: Figure 2 Imaging the Local Orientation Heterogeneity Grainmentioning
confidence: 99%
“…Our group has previously demonstrated that confocal PL maps, when measured at excitation densities below the local trap density (~10 15 cm -3 to ~10 17 cm -3 ), 12,[53][54][55] can reflect the local trap distribution in the film. 12,13 Although carrier diffusion is still important, 13,56 under such conditions, high PL intensities correspond to regions with lower trap density, and low PL intensities to regions with higher trap density. 13…”
Section: The Grains Are Identified Using 4֯ As the Threshold (B) Kmentioning
confidence: 99%
“…The findings revealed variations in local nonradiative decay rates. [139] PL intensity heterogeneity was shown when comparing confocal and widefield fluorescence microscopy methods. [132] Also, a relationship between grain boundaries and PL quenching was evidenced contradicting positive results about grain boundaries.…”
Section: Pl Correlation With Other Imaging Methodsmentioning
confidence: 99%
“…Specifically, local steady-state and time-resolved measurements show that darker regions (lower PL intensity) have greater nonradiative loss. [139] From this method, diffusion of carriers was observed outside the confocal site and showed there are intergrain transport variations. [146,147] PL intensity decreased around 65% in these regions.…”
Section: Pl Correlation With Other Imaging Methodsmentioning
confidence: 99%
See 1 more Smart Citation